Attachment of Chloroplast Polysomes to Thylakoid Membranes in Chlamydomonas reinhardtii - Chua, Nam-Hai (1973)
Treatment of synchronous cultures of Chlamydomonas reinhardtii with chloramphenicol at 4 hr after the beginning of the light phase led to a preferential loss of 70S ribosomes from the 17,000 × g(max) supernate. The “lost” 70S ribosomes were found associated with a thylakoid membrane fraction prepared from the 17,000 × g(max) pellet. Electron microscopic examinations of this fraction revealed that the 70S ribosomes were bound to the unstacked regions of the thylakoid membranes as polygonal penta- and hexamers. These bound ribosomes were only released by treatment with 500 mM KCl and puromycin, suggesting that both ionic interactions and nascent peptide chains were involved in the ribosome-membrane attachment. Since growth of the thylakoid membranes occurs in the light, it is suggested that bound chloroplast ribosomes function in the synthesis of thylakoid membrane proteins.